7x/4x+3*(8x+6)

Simple and best practice solution for 7x/4x+3*(8x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x/4x+3*(8x+6) equation:


x in (-oo:+oo)

3*(8*x+6)+((7*x)/4)*x = 0

3*(8*x+6)+(7*x^2)/4 = 0

(3*4*(8*x+6))/4+(7*x^2)/4 = 0

3*4*(8*x+6)+7*x^2 = 0

7*x^2+96*x+72 = 0

7*x^2+96*x+72 = 0

7*x^2+96*x+72 = 0

DELTA = 96^2-(4*7*72)

DELTA = 7200

DELTA > 0

x = (7200^(1/2)-96)/(2*7) or x = (-7200^(1/2)-96)/(2*7)

x = (60*2^(1/2)-96)/14 or x = (-60*2^(1/2)-96)/14

(x-((-60*2^(1/2)-96)/14))*(x-((60*2^(1/2)-96)/14)) = 0

((x-((-60*2^(1/2)-96)/14))*(x-((60*2^(1/2)-96)/14)))/4 = 0

((x-((-60*2^(1/2)-96)/14))*(x-((60*2^(1/2)-96)/14)))/4 = 0 // * 4

(x-((-60*2^(1/2)-96)/14))*(x-((60*2^(1/2)-96)/14)) = 0

( x-((-60*2^(1/2)-96)/14) )

x-((-60*2^(1/2)-96)/14) = 0 // + (-60*2^(1/2)-96)/14

x = (-60*2^(1/2)-96)/14

( x-((60*2^(1/2)-96)/14) )

x-((60*2^(1/2)-96)/14) = 0 // + (60*2^(1/2)-96)/14

x = (60*2^(1/2)-96)/14

x in { (-60*2^(1/2)-96)/14, (60*2^(1/2)-96)/14 }

See similar equations:

| .2x+27=82 | | 0.10x-.08=22 | | 3.5=m/2.6 | | 11x-9=7x+25 | | 58.52=5.6g | | 51.3=11.4u | | 131-2x=25x+20 | | 3p=26.13 | | 11+22y=0 | | b/10.4=9.2 | | 3000-120b=4000-160b | | 40+15=5x | | e/5=2.548 | | 2x^2-12x-104=0 | | 18y+36+2y+6=5 | | 8y-7=0 | | 3(2x-4)=-(x+19) | | -1/4(x-8)1/2(x+2)=x+9 | | x+x+4+x+5=33 | | x-43=-62 | | x+(-66)=-75 | | -187=a-97 | | 3+y=10 | | x+x+5+x+4=27 | | 3.5u=4u+6.28 | | x--70=95 | | -1/10(x-20)1/2(x+2)=x+9 | | 2x^2-(x-2)(x+5)=7(x+3) | | 27X^2-19X-8=0 | | 3y+8=5y-2 | | 13-9x=75-23x | | (-3y+4)-(-2y-5)=6 |

Equations solver categories